Trick or Treat? Equity Concerns in the Preliminary Feasibility Study of the Republic of Korea - Jongyearn Lee (KDI Journal of Economic Policy, 2020)
As a project appraisal tool, the preliminary feasibility study (PFS) has contributed to enhancing the efficiency of public investment decision-making in the Republic of Korea over the last two decades. To overcome the limitations of the efficiency-oriented cost-benefit analysis, the PFS accommodates equity concerns among regions, namely balanced regional development (BRD) analysis. This study attempts to gauge the contributions of BRD analysis to PFS results. Specifically, it addresses how effectively policy efforts to promote decision-making have been implemented in the PFS stage while also considering the balance between equity and efficiency in terms of the trade-off between them, the degree to which they influence the results, and whether the consideration of equity is in fact actually reflected in seriously underdeveloped regions as intended. The study finds that the PFS results over the last two decades have been largely in line with the background and policy objectives. Based on the findings of the study, needs for institutional improvement are suggested, including enhancements in the analysis of regional economic ripple effects and taking into account the psychological factors pertaining to the evaluators in the overall judgment.
Keywords: H43; H54; R53; D61; 330; Equity-efficiency Trade-off; Balanced Regional Development; Project Appraisal Preliminary Feasibility Study